(untitled) (Revista de Biblioteconomia de Brasília, 1987)
MOORE, Nick.The Library and information workforce: a study of suplly and demand. Bath: ParkerMooreLtd., 1986. 178 p.(BLR & D Report Number 5900) ISBN: 0-948960-051